Investigating the challenges of physicians\' participation in Accreditation of the hospital from the point of view of physicians working in social security hospitals - Hassan Niroomand sadabad; Ali Vafaee najar; Elahe Houshmand; Jamshid Jamali; Zahra Keyvanloo; Mahdi Dehnavi (Tehran University of Medical Sciences, 2023)
Background and purpose: Considering the important role of doctors in the implementation of accreditation standards and the necessity of their involvement in this process, this study was conducted in order to identify the views of doctors regarding the challenges of participating in accreditation programs in social security hospitals in Mashhad. Materials and methods: This study is a cross-sectional descriptive-analytical research that was conducted in two hospitals of the Social Security Organization of Mashhad, Iran. in 2022. The participants were 56 full-time working doctors with at least one year of work experience in the hospital. Data analysis was done using SPSS version 26 software. Findings: Among the challenges of doctors' participation in accreditation programs , the dimensions of the motivational mechanism (3.96±0.63) , provision of suitable resources for the implementation of accreditation (3.83±0.78), physician empowerment programs (3.78±0.73) and the role of the quality improvement office in attracting doctors' participation (3.75±0.74) were more important from the doctors' point of view, and  patients' demands (2.90±0.75) and role ambiguity 2.77±0.96), were less important in their opinion. Conclusion: Managers should consider that employee motivation and resource allocation are necessary for the effective implementation of the accreditation standard. Empowering doctors in the implementation of accreditation standards as well as the participation of quality improvement offices to interact with doctors and attract their participation are very important factors.